Analysis of elements and process of school principals' professionalization in Croatia - Relja, Renata (Array, 2019)
By combining the attributive-taxonomic and process approaches to the profession, resulting from different sociological traditions, the professional elements and the professionalization of school principals in Croatia are analysed. The research was conducted by survey method in 2017. The sample was convenient and included 73 principals who participated in the research activities of the Centre of Scientific Excellence for School Effectiveness and Management. Our results suggest that the job of school principals in Croatia cannot be considered a profession yet. There are no fundamental elements that differentiate the profession from an ordinary occupation. More specifically, there is a lack of expertise in the area of educational management and leadership (authority), cooperation with professional associations in defining the professional socialization (autonomy), as well as high social status (attractiveness) as a result of the state of previous elements. Given the contextual specificity, the discussion presents incentives, obstacles and recommendations for further professionalization of school principals in Croatia. The importance of professional education is emphasized, whose design and implementation should involve representatives of principals’ rofessional associations, as well as decentralization of education system so that theoretical expertise can be developed through the practice. As the trained practitioners focused on a benefit of the educational system stakeholders (altruism), the principals should set the conditions of the profession to make it more attractive for the best candidates.